Sporting Clays: Sport, Leisure, and Styles of Consumption - Юлия Вадимовна Харченко; Ольга Юрьевна Гурова (Journal of Economic Sociology, 2010)
The article is devoted to studying styles of consumption in the field of leisure, focusing on sporting clays which became popular among the Russian elite in the second half of 1990s.  The study demonstrates that today people with medium and low income are also engaged in sporting clays. The question arises as to whether sporting clays stimulates social differentiation or social integration. The empirical data collected from participants of a sporting clays club describe the institutionalization process of sporting clays in modern Russia, show social and economic qualities of shooters, and present a typology of people engaged in this kind of shooting